Pengembangan Usaha Kelompok Pengrajin Tenun Kain Donggala Melalui Diverifikasi Pewarnaan Alami Berbasis Daun - Pribadi, Hendra; Jusman, Jusman; Yusuf, Herlina; Jufri, Muhammad; Liana, Litna; Zakiina, Zakiina (Politeknik Negeri Cilacap, 2026)
This Community Partnership Program (PKM) addresses the main challenges faced by weavers in the Subi Group in Limboro Village, Donggala Regency. The main problems identified are limited production capacity due to outdated equipment, a lack of standardized knowledge in natural dyeing techniques, and limited capital. The solutions implemented include modernizing the looms, providing comprehensive training in the extraction and application of natural dyes based on leaves (such as jembolan, guava, mango, and teak) with precise digital measurements, and introducing electric yarn winding machines, as well as providing capital assistance for raw materials. As a result, production efficiency has increased significantly, with weaving time reduced from 30 to 40 days to just 20 days per piece of fabric. The use of natural fixatives (alum, lime, and tunjung) ensures more stable, high-quality, and environmentally friendly colors. This program has successfully improved the technical capacity of artisans and preserved local culture. Cultural heritage, empowered the community economy, and created a foundation for the development of products with Geographical Indication potential.